2006
DOI: 10.1007/s10439-005-9073-5
|View full text |Cite|
|
Sign up to set email alerts
|

A Modeling Study of Notch Noise Responses of Type III Units in the Gerbil Dorsal Cochlear Nucleus

Abstract: Abstract-A computational model of the neural circuitry of the gerbil dorsal cochlear nucleus (DCN), based on the MacGregor's neuromime model, was used to simulate type III unit (P-cell) responses to notch noise stimuli. The DCN patch model is based on a previous computational model of the cat DCN [Hancock, K. E., and H. F. Voigt. Ann. Biomed. Eng. 27:73-87, 1999]. According to the experimental study of Parsons et al. [Ann. Biomed. Eng. 29:887-896, 2001], the responses of gerbil DCN type III units to notch noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…4b-d). Reproducing salient response properties of DCN projection neurons, has also been the focus of several other modeling studies Blum et al, 1995;Franosch et al, 2003;Zheng and Voigt, 2006a;Zheng and Voigt, 2006b). Our model is similar to the model of Reed et al (1995), as it is also rate-based, whereas the more recent models of Franosch et al (2003) and Zheng and Voigt (2006b) employ spiking neurons.…”
Section: Discussionmentioning
confidence: 96%
“…4b-d). Reproducing salient response properties of DCN projection neurons, has also been the focus of several other modeling studies Blum et al, 1995;Franosch et al, 2003;Zheng and Voigt, 2006a;Zheng and Voigt, 2006b). Our model is similar to the model of Reed et al (1995), as it is also rate-based, whereas the more recent models of Franosch et al (2003) and Zheng and Voigt (2006b) employ spiking neurons.…”
Section: Discussionmentioning
confidence: 96%
“…The function of the DCN as a filter for sound localization cues has been discussed extensively in the literature (Davis et al 1996b;Ding et al 1999;May 2000;Oertel and Young 2004;Reiss and Young 2005;Young et al 1995;Young and Davis 2002;Zheng and Voigt 2006). Spectral cues from the head transfer function are thought to be combined in DCN with proprioception information to determine the location of a sound source.…”
Section: The Dcn As An Adaptive Filter For Auditory Stimulimentioning
confidence: 99%
“…However, we obtained type III-i units when the values of σ AN→P and σ I2→P are low. We have previously shown that P-cells in both gerbil and cat versions of the model are sensitive to notch noise stimuli (Zheng and Voigt 2006). These notch noises simulate the spectral notches created by the filtering properties of the external ear and are thought to be a major cue for locating sounds in the medial plane.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that we keep σ AN→P to a lower value, maybe lower than 0.5. In another work of ours, when we tried to fit the notch noise responses of P-cells to the physiological data of 15 gerbil type III units, the best σ AN→P for all 15 units was less than or equal to 0.45 (see Table 4 in Zheng and Voigt 2006). Shown in Fig.…”
Section: Response Maps Of P-cells Simulated With the Nominal Parametementioning
confidence: 94%
See 1 more Smart Citation